Developing BioFold-AR Learning Media Using Assemblr Edu to Enhance Students’ Motivation in Islamic Education - Anis Sukmawati; Ali Mudlofir; Evi Fatimatur Rusydiyah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Islamic Religious Education (IRE), particularly in Islamic history topics, continues to face challenges in enhancing student engagement and motivation to learn due to the content's abstract and narrative nature. Although Augmented Reality (AR) has the potential to provide more interactive learning experiences, its application remains largely limited to general use and has not been adequately integrated into IRE learning contexts. This study aims to develop and evaluate an AR-based learning medium, namely BioFold-AR, using the Assemblr Edu platform, to improve students’ learning motivation. This research employed a Research and Development (R&D) approach using the ADDIE model, combined with a quasi-experimental design. The study was conducted at SMP Negeri 1 Besuki Tulungagung, focusing on Islamic Cultural History material. Data were collected through expert validation, user response questionnaires, and a learning motivation instrument based on Keller’s ARCS model. The results indicate that the developed media meet the criteria of validity and practicality and are effective in significantly improving students’ learning motivation based on statistical analysis. The findings demonstrate that AR integration can enhance student engagement in IRE learning. This study offers a novel contribution by integrating low-tech AR (Assemblr Edu) with the ARCS motivational framework, thereby bridging the gap between technological accessibility and the internalization of religious values in the development of more adaptive IRE learning media. In addition, this media enables IRE teachers without programming backgrounds to independently design and develop learning media.